The INFLUENCE OF MIND MAPPING AND LEARNING MOTIVATION TOWARD WRITING ACHIEVEMENT TO THE FIFTH SEMESTER - Lianty, Nozylianty; Hakim, Arief Rahman (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
ABSTRACT This article was aimed to find out the significance average score and motivation between Mind-Mapping and Conventional Technique. Due the interpretation of this study, it found that: (1) there was a significant difference in writing achievement between the student who taught by using Mind-Mapping and those are taught using conventional technique since it was found that the result was 0.00, (2) there was significant difference in writing achievement between the students who have high motivation by using Mind-Mapping and conventional teaching since the result was 0.005, (3) there was significant difference in writing achievement between the students who have low motivation by using Mind-Mapping and conventional teaching technique since the result was 0.002, (4) there was significant difference in writing achievement between the students who have low and high motivation by using Mind-Mapping since the significant was lower 0.02, and (5) there was an interaction effect of technique used and student’s motivation in improving writing achievement since the result of interaction effect was lower 0.006. Based on the result, the writer concluded that the result of this research was lower than the level of significant level (0,05), and Mind-Mapping and motivation gave the significant influence for student’s narrative writing achievement. ABSTRAK Artikel ini bertujuan untuk mengetahui signifikansi skor rata-rata dan motivasi antara Mind-Mapping dan Teknik Konvensional. Berdasarkan interpretasi penelitian ini, ditemukan bahwa: (1) terdapat perbedaan yang signifikan dalam prestasi menulis antara siswa yang diajar menggunakan Mind-Mapping dan mereka yang diajar menggunakan teknik konvensional karena ditemukan bahwa hasilnya adalah 0,00, ( 2) terdapat perbedaan yang signifikan dalam prestasi menulis antara siswa yang memiliki motivasi tinggi dengan menggunakan Mind-Mapping dan pengajaran konvensional karena hasilnya adalah 0,005, (3) terdapat perbedaan yang signifikan dalam prestasi menulis antara siswa yang memiliki motivasi rendah dengan menggunakan Mind -Pemetaan dan teknik pengajaran konvensional karena hasilnya adalah 0,002, (4) terdapat perbedaan yang signifikan dalam prestasi menulis antara siswa yang memiliki motivasi rendah dan tinggi dengan menggunakan Mind-Mapping karena signifikansinya lebih rendah 0,02, dan (5) terdapat peningkatan efek interaksi teknik yang digunakan dan motivasi siswa dalam meningkatkan prestasi menulis karena hasil efek interaksi lebih rendah 0,006. Berdasarkan hasil tersebut, penulis menyimpulkan bahwa hasil penelitian ini lebih rendah dari tingkat signifikansi (0,05), dan Mind-Mapping dan motivasi memberikan pengaruh yang signifikan terhadap prestasi menulis narasi siswa.